Preparation method and application of red carbon composite graphite phase carbon nitride photocatalytic material

By recombining the red carbon semiconductor with graphite phase carbon nitride (g-C3N4) to construct a red carbon composite g-C3N4 heterojunction photocatalyst, the problem of high recombination of photogenerated carriers and narrow visible light response range of a single g-C3N4 photocatalyst in the field of photocatalytic hydrogen production is solved, and efficient photocatalytic decomposition of water to produce hydrogen.

CN119746903APending Publication Date: 2025-04-04ZHEJIANG HUAYUAN PIGMENT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411703027.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the field of photocatalytic hydrogen production, single graphite phase carbon nitride (g-C3N4) photocatalysts face the problems of high recombination of photogenerated carriers and narrow visible light response range, and it is difficult to achieve the 10% energy conversion efficiency required by commercialization.

Method used

By recombining the red carbon semiconductor with graphite phase carbon nitride (g-C3N4), a red carbon composite g-C3N4 heterojunction photocatalyst was constructed, and the visible light response was enhanced by the narrow band gap and high conjugated structure of the red carbon, and the charge separation efficiency was improved through the heterostructure.

Benefits of technology

A photocatalyst with high visible light response and low carrier recombination rate has been achieved, which significantly improves the hydrogen yield of photocatalytic decomposition of water to produce hydrogen, and can effectively replace the existing photohydrogen catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746903A_ABST
    Figure CN119746903A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a red carbon composite graphite phase carbon nitride photocatalytic material, comprising the following steps: S1, preparing a red carbon semiconductor: dissolving malonic acid in anhydride, reacting at a certain temperature by condensation reflux to obtain a product solution, dropping the solution into diethyl ether to obtain a solid precipitate, and washing with diethyl ether to obtain a red carbon semiconductor; S2, preparing a graphite phase carbon nitride: calcining a carbon nitrogen compound at a high temperature to obtain a graphite phase carbon nitride g-C3N4; S3, preparing a red carbon / g-C3N4 photocatalyst: compounding the red carbon semiconductor obtained in S1 with the graphite phase carbon nitride g-C3N4 obtained in S2 by an ultrasound-assisted method to obtain a red carbon / g-C3N4 photocatalyst. The red carbon composite g-C3N4 photocatalyst obtained in this scheme integrates the advantages of heterogeneous structure to improve charge separation efficiency and narrow bandgap red carbon to enhance visible light response, which is conducive to promoting photolysis of water to produce hydrogen, and the structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a preparation method and application of a red carbon composite graphite phase carbon nitride photocatalytic material. Background Art

[0002] As a new type of clean energy, hydrogen is widely used in chemical, electronic, metallurgical and other fields. At present, hydrogen is mainly produced in industry through water-gas conversion reaction, which not only emits a large amount of carbon dioxide, but also consumes a lot of heat energy. Photocatalytic technology uses solar energy to drive water decomposition to produce hydrogen, directly converting low-density solar energy into hydrogen energy storage, achieving net zero carbon emissions in the hydrogen energy industry chain, and is a very promising hydrogen production technology.

[0003] At present, in order to promote the application of photocatalytic hydrogen production technology, the development of photocatalytic materials with visible light response and high quantum efficiency is the research focus. Among them, graphitic carbon nitride (g-C3N4) has attracted much attention in the field of photocatalytic hydrogen production due to its visible light response band gap of about 2.7eV, suitable energy band structure, high stability, environmental protection, non-toxicity, and abundant sources. However, the single g-C3N4 system faces the problems of high recombination of photogenerated carriers and narrow visible light response range, making it difficult to achieve the 10% energy conversion efficiency required for commercialization. Therefore, researchers have done a lot of research on the improvement and optimization of g-C3N4 photocatalysts and have made good progress. Among them, the construction of heterostructures is an optimization strategy that has been adopted more in recent years. By compounding g-C3N4 with another semiconductor material to form a Z-type or S-type heterostructure with an interface built-in electric field, the photogenerated electrons and holes are enriched on the two semiconductors respectively, realizing the spatial separation of photogenerated carriers, thereby improving the charge separation efficiency and promoting the photocatalytic reaction.

[0004] Recently, researchers have reported a deep red-brown carbon-based semiconductor material, "red carbon", which is p(C3O2) formed by the polymerization of carbon dioxide molecules. x Semiconductors have the characteristics of high conjugated structure, narrow band gap, easy preparation, low toxicity, etc., and their band gap is only about 1.7eV, which has great application potential in the field of photocatalysis. In particular, the excellent light absorption ability of red carbon semiconductors can greatly broaden the visible light response range of g-C3N4, and at the same time generate abundant photogenerated electrons to participate in the hydrogen evolution reaction, which is expected to further improve the photocatalytic hydrogen production performance of g-C3N4. Summary of the invention

[0005] In order to solve the above-mentioned technical problems, the purpose of the present invention is to provide a preparation method and application of a red carbon composite graphite phase carbon nitride photocatalytic material, integrate the advantages of heterostructure and red carbon photoresponse, composite red carbon semiconductor with g-C3N4, and construct a new type of g-C3N4 heterojunction photocatalyst with high visible light response and low carrier recombination rate, and use it for photocatalytic water decomposition to produce hydrogen.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0007] A method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material comprises the following steps:

[0008] S1. Preparation of a red carbon semiconductor: dissolving malonic acid in anhydride, subjecting the mixture to a condensation reflux reaction at a certain temperature to obtain a product solution, adding the solution dropwise into diethyl ether to obtain a solid precipitate, and washing the solid precipitate with diethyl ether to obtain a red carbon semiconductor;

[0009] S2, preparing graphite phase carbon nitride: calcining carbon nitrogen compound at high temperature to obtain graphite phase carbon nitride g-C3N4;

[0010] S3. Preparation of red carbon / g-C3N4 photocatalyst: The red carbon semiconductor obtained in S1 is compounded with the graphite phase carbon nitride g-C3N4 obtained in S2 by an ultrasound-assisted method to obtain a red carbon / g-C3N4 photocatalyst.

[0011] Preferably, the molar ratio of malonic acid to acid anhydride is 1:0.5-20.

[0012] Preferably, the acid anhydride is one of formic anhydride and acetic anhydride.

[0013] Preferably, in S1, malonic acid is dissolved in acid anhydride and then reacted at 100-160° C. for 1 to 10 hours.

[0014] Preferably, in S1, the washing times with diethyl ether are 1 to 5 times, and after washing with diethyl ether, the mixture is vacuum dried at 60 to 90° C. to obtain a dark red-brown red carbon semiconductor.

[0015] Preferably, in S2, the carbon nitrogen compound is placed in a porcelain boat, covered and calcined in a muffle furnace at 500-650°C for 2-5 hours with a heating rate of 2-10°C / min. After the calcination, the light yellow graphite phase carbon nitride g-C3N4 can be obtained by naturally cooling the temperature.

[0016] Preferably, the carbon-nitrogen compound is one of urea, cyanamide, melamine and tertiary cyanamide.

[0017] Preferably, in S3, the red carbon semiconductor and the graphite phase carbon nitride g-C3N4 are ultrasonically dispersed in deionized water for 30 to 120 minutes respectively, and then the dispersed solutions are mixed, and the red carbon and graphite phase carbon nitride g-C3N4 are further self-assembled and composited using ultrasound to obtain a red carbon composite g-C3N4 photocatalyst.

[0018] Preferably, the mass ratio of graphite phase carbon nitride g-C3N4 and red carbon semiconductor is 1:0.01-10.

[0019] The photocatalyst prepared by the method for preparing the red carbon composite graphite phase carbon nitride photocatalytic material as described above is used in photocatalytic water decomposition to produce hydrogen.

[0020] The present invention has the following beneficial effects due to the adoption of the above technical solution:

[0021] 1. The present invention prepares red carbon semiconductors by a simple liquid phase method, and the preparation method is simple. Then, the red carbon semiconductor is compounded with graphite phase carbon nitride g-C3N4 through an ultrasonic-assisted process to obtain a red carbon composite g-C3N4 heterojunction photocatalyst. The red carbon composite g-C3N4 photocatalyst integrates the advantages of heterostructure to improve charge separation efficiency and narrow bandgap red carbon to enhance visible light response, which is beneficial to promote photocatalytic water splitting to produce hydrogen.

[0022] 2. Compared with existing materials and technologies, the present invention provides a new type of red carbon composite g-C3N4 heterojunction photocatalyst that is environmentally friendly, non-toxic, has high visible light response, and low carrier recombination. The preparation process is simple and easy to operate. The yield of red carbon semiconductor prepared by a simple liquid phase method is about 10% to 20%, and the yield of graphite phase carbon nitride g-C3N4 prepared by a high-temperature thermal polymerization method is about 50% to 70%, which is suitable for industrial production.

[0023] 3. The hydrogen yield of the red carbon composite g-C3N4 photocatalyst prepared by the method of the present invention is more than 9500 times that of the red carbon semiconductor and more than 2 times that of the graphite phase carbon nitride g-C3N4, and can effectively replace the existing photocatalyst for water splitting. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD diagrams of the red carbon semiconductor, graphite phase carbon nitride g-C3N4 and red carbon composite g-C3N4 photocatalyst in the present invention;

[0025] Figure 2 It is the UV-visible diffuse reflectance spectrum of the graphite phase carbon nitride g-C3N4 and red carbon composite g-C3N4 photocatalyst in the present invention;

[0026] Figure 3It is a fluorescence spectrum diagram (excitation wavelength 325nm) of the graphite phase carbon nitride g-C3N4 and red carbon composite g-C3N4 photocatalyst in the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0028] Embodiment 1:

[0029] This embodiment provides a method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material, comprising the following steps:

[0030] S1. Preparation of red carbon semiconductor by liquid phase method: First, 0.05 mol malonic acid and 0.25 mol acetic anhydride were mixed evenly, and the malonic acid was fully dissolved at 90°C. Then, the above solution was heated to 140°C for reaction for 5 hours, and magnetic stirring and condensation reflux were performed throughout the reaction process to ensure sufficient reaction. After the reaction was completed, the obtained reddish-brown viscous liquid was slowly added dropwise to diethyl ether to obtain a solid product precipitate. The solid product was repeatedly washed with diethyl ether solution 3 times, and then vacuum dried at 80°C to obtain a dark reddish-brown red carbon semiconductor.

[0031] S2. Prepare graphite phase carbon nitride by high temperature thermal polymerization: Place urea in a porcelain boat, cover it and bake it in a muffle furnace at 550°C for 4 hours with a heating rate of 10°C / min. After baking, cool it naturally to obtain a light yellow graphite phase carbon nitride g-C3N4 sample.

[0032] S3. Preparation of red carbon / g-C3N4 photocatalyst: First, 1 mg of red carbon semiconductor and 50 mg of graphite phase carbon nitride g-C3N4 were dispersed in 30 mL of deionized water respectively, and the two solutions were mixed after 30 min of ultrasonic treatment. The red carbon and graphite phase carbon nitride g-C3N4 were further ultrasonically treated for 30 min to assist the self-assembly and composite of the red carbon and the graphite phase carbon nitride g-C3N4 to obtain a red carbon composite g-C3N4 photocatalyst.

[0033] Embodiment 2:

[0034] This embodiment provides a method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material, comprising the following steps:

[0035] S1. Preparation of red carbon semiconductor by liquid phase method: First, 0.05 mol malonic acid and 0.25 mol acetic anhydride were mixed evenly, and the malonic acid was fully dissolved at 90°C. Then, the above solution was heated to 140°C for reaction for 5 hours, and magnetic stirring and condensation reflux were performed throughout the reaction process to ensure sufficient reaction. After the reaction was completed, the obtained reddish-brown viscous liquid was slowly added dropwise to diethyl ether to obtain a solid product precipitate. The solid product was repeatedly washed with diethyl ether solution 3 times, and then vacuum dried at 80°C to obtain a dark reddish-brown red carbon semiconductor.

[0036] S2. Prepare graphite phase carbon nitride by high temperature thermal polymerization: Place urea in a porcelain boat, cover it and bake it in a muffle furnace at 550°C for 4 hours with a heating rate of 10°C / min. After baking, cool it naturally to obtain a light yellow graphite phase carbon nitride g-C3N4 sample.

[0037] S3. Preparation of red carbon / g-C3N4 photocatalyst: First, 2.5 mg of red carbon semiconductor and 50 mg of graphite phase carbon nitride g-C3N4 were dispersed in 30 mL of deionized water respectively, and the two solutions were mixed after 30 min of ultrasonic treatment. Further ultrasonic treatment was performed for 30 min to assist the self-assembly and composite of red carbon and graphite phase carbon nitride g-C3N4 to obtain a red carbon composite g-C3N4 photocatalyst.

[0038] Embodiment 3:

[0039] This embodiment provides a method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material, comprising the following steps:

[0040] S1. Preparation of red carbon semiconductor by liquid phase method: First, 0.05 mol malonic acid and 0.25 mol acetic anhydride were mixed evenly, and the malonic acid was fully dissolved at 90°C. Then, the above solution was heated to 140°C for reaction for 5 hours, and magnetic stirring and condensation reflux were performed throughout the reaction process to ensure sufficient reaction. After the reaction was completed, the obtained reddish-brown viscous liquid was slowly added dropwise to diethyl ether to obtain a solid product precipitate. The solid product was repeatedly washed with diethyl ether solution 3 times, and then vacuum dried at 80°C to obtain a dark reddish-brown red carbon semiconductor.

[0041] S2. Prepare graphite phase carbon nitride by high temperature thermal polymerization: Place urea in a porcelain boat, cover it and bake it in a muffle furnace at 550°C for 4 hours with a heating rate of 10°C / min. After baking, cool it naturally to obtain a light yellow graphite phase carbon nitride g-C3N4 sample.

[0042] S3. Preparation of red carbon / g-C3N4 photocatalyst: First, 5 mg of red carbon semiconductor and 50 mg of graphite phase carbon nitride g-C3N4 were dispersed in 30 mL of deionized water respectively, and the two solutions were mixed after 30 min of ultrasonic treatment. Further ultrasonic treatment was performed for 30 min to assist the self-assembly and composite of red carbon and graphite phase carbon nitride g-C3N4 to obtain a red carbon composite g-C3N4 photocatalyst.

[0043] Embodiment 4:

[0044] This embodiment provides a method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material, comprising the following steps:

[0045] S1. Preparation of red carbon semiconductor by liquid phase method: First, 0.05 mol malonic acid and 0.25 mol acetic anhydride were mixed evenly, and the malonic acid was fully dissolved at 90°C. Then, the above solution was heated to 140°C for reaction for 5 hours, and magnetic stirring and condensation reflux were performed throughout the reaction process to ensure sufficient reaction. After the reaction was completed, the obtained reddish-brown viscous liquid was slowly added dropwise to diethyl ether to obtain a solid product precipitate. The solid product was repeatedly washed with diethyl ether solution 3 times, and then vacuum dried at 80°C to obtain a dark reddish-brown red carbon semiconductor.

[0046] S2. Prepare graphite phase carbon nitride by high temperature thermal polymerization: Place urea in a porcelain boat, cover it and bake it in a muffle furnace at 550°C for 4 hours with a heating rate of 10°C / min. After baking, cool it naturally to obtain a light yellow graphite phase carbon nitride g-C3N4 sample.

[0047] S3. Preparation of red carbon / g-C3N4 photocatalyst: First, 12.5 mg of red carbon semiconductor and 50 mg of graphite phase carbon nitride g-C3N4 were dispersed in 30 mL of deionized water respectively, and the two solutions were mixed after 30 min of ultrasonic treatment. Further ultrasonic treatment was performed for 30 min to assist the self-assembly and composite of red carbon and graphite phase carbon nitride g-C3N4 to obtain a red carbon composite g-C3N4 photocatalyst.

[0048] Embodiment 5:

[0049] This embodiment provides a method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material, comprising the following steps:

[0050] S1. Preparation of red carbon semiconductor by liquid phase method: First, 0.05 mol malonic acid and 0.25 mol acetic anhydride were mixed evenly, and the malonic acid was fully dissolved at 90°C. Then, the above solution was heated to 140°C for reaction for 5 hours, and magnetic stirring and condensation reflux were performed throughout the reaction process to ensure sufficient reaction. After the reaction was completed, the obtained reddish-brown viscous liquid was slowly added dropwise to diethyl ether to obtain a solid product precipitate. The solid product was repeatedly washed with diethyl ether solution 3 times, and then vacuum dried at 80°C to obtain a dark reddish-brown red carbon semiconductor.

[0051] S2. Prepare graphite phase carbon nitride by high temperature thermal polymerization: Place urea in a porcelain boat, cover it and bake it in a muffle furnace at 550°C for 4 hours with a heating rate of 10°C / min. After baking, cool it naturally to obtain a light yellow graphite phase carbon nitride g-C3N4 sample.

[0052] S3. Preparation of red carbon / g-C3N4 photocatalyst: First, 21.5 mg of red carbon semiconductor and 50 mg of graphite phase carbon nitride g-C3N4 were dispersed in 30 mL of deionized water respectively, and the two solutions were mixed after 30 min of ultrasonic treatment. Further ultrasonic treatment was performed for 30 min to assist the self-assembly and composite of red carbon and graphite phase carbon nitride g-C3N4 to obtain a red carbon composite g-C3N4 photocatalyst.

[0053] Embodiment 6:

[0054] This embodiment provides a method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material, comprising the following steps:

[0055] S1. Preparation of red carbon semiconductor by liquid phase method: First, 0.05 mol malonic acid and 0.25 mol acetic anhydride were mixed evenly, and the malonic acid was fully dissolved at 90°C. Then, the above solution was heated to 140°C for reaction for 5 hours, and magnetic stirring and condensation reflux were performed throughout the reaction process to ensure sufficient reaction. After the reaction was completed, the obtained reddish-brown viscous liquid was slowly added dropwise to diethyl ether to obtain a solid product precipitate. The solid product was repeatedly washed with diethyl ether solution 3 times, and then vacuum dried at 80°C to obtain a dark reddish-brown red carbon semiconductor.

[0056] S2. Prepare graphite phase carbon nitride by high temperature thermal polymerization: Place urea in a porcelain boat, cover it and bake it in a muffle furnace at 550°C for 4 hours with a heating rate of 10°C / min. After baking, cool it naturally to obtain a light yellow graphite phase carbon nitride g-C3N4 sample.

[0057] S3. Preparation of red carbon / g-C3N4 photocatalyst: First, 50 mg of red carbon semiconductor and 50 mg of graphite phase carbon nitride g-C3N4 were dispersed in 30 mL of deionized water respectively, and the two solutions were mixed after 30 min of ultrasonic treatment. Further ultrasonic treatment was performed for 30 min to assist the self-assembly and composite of red carbon and graphite phase carbon nitride g-C3N4 to obtain a red carbon composite g-C3N4 photocatalyst.

[0058] The crystal phase structure of the red carbon composite g-C3N4 photocatalyst in Example 2 and Example 6 was analyzed by X-ray diffraction analyzer, and the following results were obtained: Figure 1 The X-ray diffraction pattern shown. Figure 1 It can be seen that the red carbon composite g-C3N4 photocatalyst showed obvious g-C3N4 diffraction peaks at 12.8° and 27.6°, and the characteristic diffraction peaks of red carbon at 19.3° and 24.9° can also be observed in the system with high red carbon content, indicating that the red carbon composite g-C3N4 photocatalyst was successfully prepared. However, the system with low red carbon content did not show red carbon diffraction peaks, which may be because the diffraction peak signal of pure red carbon is relatively weak and not easy to appear in the low red carbon system.

[0059] Figure 2 This is the UV-visible diffuse reflectance spectrum of the red carbon composite g-C3N4 photocatalyst prepared in Example 2. It can be seen from the figure that compared with the graphite phase carbon nitride g-C3N4, the light absorption of the red carbon composite g-C3N4 in the range of 400-800nm ​​is significantly enhanced, indicating that the utilization rate of visible light is improved, thereby improving the photocatalytic efficiency.

[0060] Figure 3 This is the fluorescence spectrum of the red carbon composite g-C3N4 photocatalyst prepared in Example 2 (excitation wavelength 325nm). Generally speaking, the fluorescence of semiconductor samples is generated by the recombination of photogenerated electrons and holes. Figure 3 It can be seen that the red carbon composite g-C3N4 exhibits a significantly reduced fluorescence intensity, indicating that the composite of red carbon effectively inhibits the recombination of photogenerated charges, improves the separation efficiency of photogenerated charges, and promotes the photocatalytic reaction.

[0061] Application Example 1:

[0062] An aqueous solution containing a sacrificial agent and a platinum-containing compound is used as a photocatalytic water decomposition hydrogen production model, and the prepared samples are evaluated for the performance of visible light photocatalytic water decomposition hydrogen production. Among them, the amount of red carbon composite g-C3N4 photocatalyst is 5-500 mg, the reaction solution is 10-200 mL, the sacrificial agent is one of methanol aqueous solution, triethanolamine aqueous solution and lactic acid aqueous solution, and the platinum-containing compound refers to one of chloroplatinic acid, platinum chloride, potassium chloroplatinate and sodium chloroplatinate. Before illumination, the system is ultrasonically dispersed for 5-60 minutes, and argon is passed for 10-60 minutes to remove air. The entire reaction is carried out in a top-irradiated quartz reactor. The system first deposits Pt co-catalyst under illumination for 60-180 minutes, and the deposition amount is 0.2-3wt% Pt, with a mass content relative to the red carbon composite g-C3N4 photocatalyst. Subsequently, 10-1000 μL of gas is extracted every 30-60 minutes, and the product is qualitatively and quantitatively analyzed by gas chromatography, the carrier gas of the gas chromatography is argon, and the detector is TCD.

[0063] Specifically, in this application example, 20 mg of red carbon composite g-C3N4 photocatalyst was added to 45 mL of an aqueous solution containing 10% triethanolamine sacrificial agent and 1.02 μmol of chloroplatinic acid, and the photocatalytic water evolution performance test was carried out in a top-irradiated quartz reactor at room temperature. Before illumination, the reaction system was ultrasonicated for 20 minutes to evenly disperse the photocatalyst, and then argon was passed through for 20 minutes to remove the air in the reactor, and then the reactor was closed. Before the formal reaction, Pt co-catalyst deposition was carried out for 120 minutes, and then 0.2 mL of gas product was extracted every 60 minutes for analysis by gas chromatography. The gas chromatograph used was FULI GC7980, argon was used as the carrier gas, and TCD was used as the detector.

[0064] The hydrogen production rates of the red carbon composite g-C3N4 photocatalysts prepared at different composite ratios in Examples 1-6 were tested, and the test results are shown in Table 1 below:

[0065] Table 1: Comparison of photocatalytic hydrogen production rates of red carbon composite g-C3N4 photocatalysts prepared in Examples 1-6

[0066]

[0067]

[0068] As shown in Table 1 above, the hydrogen production rate of the red carbon composite g-C3N4 photocatalyst is higher than that of pure g-C3N4 and red carbon, indicating that the composite of red carbon is beneficial to the improvement of the photocatalytic performance of graphite phase carbon nitride. At the same time, with the increase of the composite amount of red carbon, the photocatalytic performance of the red carbon composite g-C3N4 photocatalyst first increases and then decreases slightly. When the mass ratio of red carbon to g-C3N4 is 0.05, the photocatalytic performance of the red carbon composite g-C3N4 photocatalyst is the best, and the hydrogen production rate reaches 2854.0μL / h. Its hydrogen evolution rate is significantly higher than that of the original pure g-C3N4, which is about 2.1 times higher.

[0069] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Ordinary technicians in the field can change, modify, replace, modify, delete some features, add features or re-combine features to form a technical solution in the above embodiments without departing from the principles and purpose of the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the innovative principles of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material, characterized in that: The steps include: S1. Preparation of a red carbon semiconductor: dissolving malonic acid in anhydride, subjecting the mixture to a condensation reflux reaction at a certain temperature to obtain a product solution, adding the solution dropwise into diethyl ether to obtain a solid precipitate, and washing the solid precipitate with diethyl ether to obtain a red carbon semiconductor; S2, preparing graphite phase carbon nitride: calcining carbon nitrogen compound at high temperature to obtain graphite phase carbon nitride g-C3N4; S3. Preparation of red carbon / g-C3N4 photocatalyst: The red carbon semiconductor obtained in S1 is compounded with the graphite phase carbon nitride g-C3N4 obtained in S2 by an ultrasound-assisted method to obtain a red carbon / g-C3N4 photocatalyst.

2. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 1, characterized in that: The molar ratio of malonic acid to acid anhydride is 1:0.5-20.

3. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 1, characterized in that: The acid anhydride is one of formic anhydride and acetic anhydride.

4. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 1, characterized in that: In S1, malonic acid is dissolved in anhydride and reacted at 100-160°C for 1-10 hours.

5. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 1, characterized in that: In S1, the washing times of diethyl ether are 1 to 5 times, and after washing with diethyl ether, vacuum drying is performed at 60 to 90°C to obtain a dark red-brown red carbon semiconductor.

6. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 1, characterized in that: In S2, the carbon and nitrogen compounds are placed in a porcelain boat, covered and calcined in a muffle furnace at 500-650°C for 2-5 hours with a heating rate of 2-10°C / min. After the calcination, the light yellow graphite phase carbon nitride g-C3N4 is obtained by naturally cooling the temperature.

7. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 6, characterized in that: The carbon-nitrogen compound is one of urea, cyanamide, melamine and tertiary cyanamide.

8. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 1, characterized in that: In S3, the red carbon semiconductor and the graphite phase carbon nitride g-C3N4 are ultrasonically dispersed in deionized water for 30 to 120 minutes respectively, and then the dispersed solutions are mixed, and the red carbon and graphite phase carbon nitride g-C3N4 are further self-assembled and composited using ultrasound for 30 to 120 minutes to obtain a red carbon composite g-C3N4 photocatalyst.

9. The method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material according to claim 8, characterized in that: The mass ratio of graphite phase carbon nitride g-C3N4 and red carbon semiconductor is 1:0.01-10.

10. Use of the photocatalyst prepared by the method for preparing a red carbon composite graphite phase carbon nitride photocatalytic material as claimed in claim 1 in photocatalytic water decomposition to produce hydrogen.

Citation Information

Cited By

  • Quaternary ammonium modified iron-doped graphite phase carbon nitride Fenton catalyst as well as preparation method and application thereof

    CN121648949A